Analisis Faktor-Faktor Yang Dipertimbangkan Konsumen Dalam Keputusan Pembelian Minyak Goreng Bimoli Di Pasar Swalayan Kabupaten Wonogiri - Yenny Sundari; Mohd. Harisudin; Agustono Agustono (Universitas Sebelas Maret, 2018)
The research aims to find out the considered factors and the dominant variables which considered by consumers into buying Bimoli’s cooking oil at supermarket in Wonogiri regency. The basic method in this research is analytical descriptive with survey techniques. Location research purposively determined. The sampling method used was judgment sampling and data analysis method used is factor analysis. The data used are primary data and secondary data. The results of factor analysis showed that there are 7 factors that become consumer consideration in buying Bimoli cooking oil product at supermarket in Wonogiri regency. The seven factors are based on their priorities are product factors, individual factors, promotion factors, packaging factors, process factors, place factors, and psychological factors. The dominant variables considered by consumer are clarity variable on product factor, variable of income level on individual factor, advertisement display variable on promotion factor, image variable and color of packaging on packing factor, service variable on process factor, comfort variable at place factor, and Confidence variable on psychological factors.